Utilizing Machine Learning for Intrusion Detection Systems in the Context of Cloud Computing - Mohammed Akif; Anuj Nakka; Solanki Prakash; Vijay N; Dr Suresh Kallam (International Journal of Advanced Research in Science, Communication and Technology, 2023)
The rapid advancements in the internet and communication sectors have led to a huge expansion in the network dimension and the related data. The proliferation of new assault kinds as a result makes it challenging for community safety to accurately identify invasions. Furthermore, the presence of intruders who want to launch a lot of attacks against the network cannot be ignored. An intrusion detection device (IDS) is one such instrument that protects against prospective intrusions by monitoring community communication to guarantee its confidentiality, integrity, and availability. IDS continues to struggle with innovative intrusion detection, lowering false alarm rates, and improving detection accuracy despite substantial research backing. An intrusion detection system's main job is to protect resources against threats. It predicts user behaviour based on analysis, and determines whether that behaviour constitutes an assault or is simply normal behaviour. We use Support Vector Machine (SVM) and Rough Set Theory (RST) to detect network breaches (SVM). Computer learning (ML) and Python-based total IDS systems are recently being employed to identify intrusions across the network in an ecologically friendly manner. The taxonomy presented in this article is mostly based on the impressive machine learning and Python approaches used to develop network-based IDS (NIDS) systems. The article begins by defining IDS.